Superior Human Resource Development through Product Innovation Management: The Effect of Training, Skills, Competence, and Technology - Lapiti Gokmatua Sagala; Rifqah Harahap; Mhd Restu Razaq (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Increasing business competition demands innovation and high-quality human resource development. This study examines the effect of training, skills, competence, and technology on superior human resource development through product innovation management in food Small and Medium Enterprises (SMEs) in Labuhanbatu Regency. This study used a quantitative survey approach involving 127 food SMEs in Labuhanbatu Regency selected through saturated sampling. Data were collected using Likert-scale questionnaires and analyzed with SEM-PLS using SmartPLS. The results show that training, skills, competence, and technology have positive and significant effects on product innovation management. In addition, these four variables also have positive and significant effects on superior human resource development. Product innovation management has been shown to have a positive and significant effect on superior human resource development and to mediate the effects of training, skills, competence, and technology on it. The R-square value indicates that training, skills, competence, and technology explain 67.8% of the variance in product innovation management, while superior human resource development explains 72.4% of the variance in the model. These findings confirm that superior human resource development in food SMEs should be supported by relevant training, skill improvement, competence strengthening, technology utilization, and sustainable product innovation management.